Identifying and Estimating Neighborhood Effects - Graham, Bryan S. (Journal of Economic Literature, 2018)
Residential segregation by race and income are enduring features of urban America. Understanding the effects of residential segregation on educational attainment, labor market outcomes, criminal activity, and other outcomes has been a leading project of the social sciences for over half a century. This paper describes techniques for measuring the effects of neighborhood of residence on long-run life outcomes. ( JEL C51, I24, J15, K42, R23)